2021
DOI: 10.1002/jcb.30018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant activated soluble adenylate cyclase of Leishmania donovani regulates the cAMP–PKA signaling axis for its intra‐macrophage survival during infection

Abstract: Adenosine 3',5'-cyclic monophosphate (cAMP) is a stress sensor molecule that transduces the cellular signal when Leishmania donovani moves from insect vector to mammalian host. At this stage, the parasite membrane-bound receptor adenylate cyclase predominantly produces cAMP to cope with the oxidative assault imposed by host macrophages. However, the role of soluble adenylate cyclase of L. donovani (LdHemAC) has not been investigated fully. In the present investigation, we monitored an alternative pool of cAMP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The PKA gene has been reported in previous studies to have the ability to participate as a second messenger and to help Plasmodium invade the host cell (Flueck et al ., 2019 ; Patel et al ., 2019 ; Kumar et al ., 2021 ). In the previous study, we found a significant upregulation of the expression level of β-PKA gene by the transcriptome analysis after the pre-infestation of P. apodigitiformis on ornamental fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PKA gene has been reported in previous studies to have the ability to participate as a second messenger and to help Plasmodium invade the host cell (Flueck et al ., 2019 ; Patel et al ., 2019 ; Kumar et al ., 2021 ). In the previous study, we found a significant upregulation of the expression level of β-PKA gene by the transcriptome analysis after the pre-infestation of P. apodigitiformis on ornamental fish.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that protein kinase A (PKA) is a prominent member of the AGC kinase family. β-PKA controls a variety of cellular metabolism processes, including cell growth, gene expression and metabolism (Leroux et al ., 2018 ; Kumar et al ., 2021 ). Therefore, β-PKA can play an important role in various infection and toxicological processes.…”
Section: Introductionmentioning
confidence: 99%